What the heck? – hacking HEK. - Lynch IRL, Garrett (Performance Research)
In the last week of voting in 2018, I created and deployed an auto-clicking application or bot (fig. 1) to simulate user clicks and cast more than a thousand votes for a nominated artist's work. - hacking HEK (2018) including HEK's website (top-right), poll (top-left), auto-clicking application (centre-right), screen recording and statement posted on social media (bottom-right) and HEK's press statement (bottom-left). Votes for the audience prize were cast through a web-based poll system on HEK's website that was anonymously hacked in 2017 with first and second places surpassing other nominations by more than 1,400 votes.